“No German, No Service”: EU Migrants’ Unequal Access to Welfare Entitlements in Germany - Ratzmann, Nora (2022)
While existing research has analysed the intersecting migration and social security law, which stratifies migrants’ formal social entitlements, less work has been done on the informal stratifications beyond the law that determine substantive social rights. This article illustrates the informal barriers to de facto benefit receipt that intra‐EU migrant citizens may experience when claiming social assistance in local German job centres, regardless of their manifest legal entitlements. Focussing on informal, yet commonly institutionalised practices of language discrimination, analysis of 103 qualitative, in‐depth interviews reveal recurring patterns of administrative exclusion beyond individual instances of discriminatory behaviour. The unwritten rules and everyday practices shaping administrators’ claims‐processing routines often go against what the law or administrative procedures proscribe, and could be considered as forms of discrimination. The former may be explained by institutional constraints, such as a performance‐orientedmanagement culture, legalistic claims‐processing, or superficial diversity policies. By shedding light on how inequalities in access are constructed in daily administrative practice, this article adds to existing empirical knowledge on how informal inequalities in access emerge at different stages of the benefit claiming process, in contrast to formal social rights on paper, as well as social administrations’ handling of diversity in a context of transnational social protection.